Effectiveness of manuka honey and chlorhexidine mouthwash on gingivitis and Streptococcus Mutans count among children: A randomized controlled trial - K S Sruthi; R Yashoda; P Manjunath Puranik (Wolters Kluwer Medknow Publications, 2021)
Background: Chlorhexidine is considered a gold standard among the chemical plaque control measures. Recently, a search for a natural alternative having similar effectiveness of that of chlorhexidine is gaining importance due to various side effects reported. Honey is a natural product with antibacterial properties that can be used to improve oral health. Manuka honey (MH) is considered superior due to its antibacterial properties. However, studies pertaining to effectiveness of MH and chlorhexidine on oral health are limited. Aim: This study aimed to evaluate the effectiveness of MH and 0.2% chlorhexidine digluconate (CHX) mouthwash on reducing gingivitis and Streptococcus mutans count (SM). Materials and Methods: A randomized controlled trial blinded study was conducted among 12-15 years old children with (Decayed, Missing, Filled Teeth) scores of 1-4, plaque and gingival scores of 1-2 were selected, and an equal number of children (30 each) were randomly allocated to MH and CHX groups. Participants were instructed to rinse 5 ml of MH and 10 ml of CHX twice daily for 14 days. Unstimulated saliva was collected from the children, and plaque and gingival indices were assessed at baseline, 7th day, and 14th day. Unstimulated saliva was subjected to microbiological analysis for SM. Student's t-test and repeated-measures analysis of variance test were applied for inter- and intragroup comparison, respectively. P < 0.05 was considered significant. Results: There was no statistically significant difference in plaque and gingival scores and SM count between the groups at baseline, 7th day, and 14th day. Statistically significant reductions (P < 0.01) in plaque, gingival scores, and SM count were observed in both the groups at 7th and 14th day from baseline. No adverse events were reported during the trial. Conclusion: Effectiveness of MH was comparable with CHX mouthwash in reducing gingivitis and SM count. MH seems to be a promising antimicrobial agent effective in improving gingival health and reducing caries risk.